Applications of Biological and Physiological Signals in Commercial Video Gaming and Game Research: A Review - Hughes, Alayna; Jorda, Sergi (Frontiers in Computer Science, 2021)
Video gaming is now available as a fully immersive experience that creates responsive inputs and outputs concerning the user, and some experimental developers have integrated the use of the voice, brain, or muscles as input controls. The use of physiological signal equipment can provide valuable information regarding the emotion of a player or patient during gameplay. In this article, we discuss five of the most common biosignals that are used in gaming research, and their function and devices that may be used for measurement. We break down those individual signals and present examples of research studies that implement them. We also discuss the usage of biological signals within commercial gaming and conclude with some possible future directions for the use of biological signals in gaming and game research.